Role of AI and Machine Learning in Enhancing Mental Health Care - Kumar, Sanjay; Radhakrishnan, Venkateswaran; Nimma, Divya; Tamilarasi, K.; Kumar, Pramod; Florence, M. Mary Victoria (South Eastern European Journal of Public Health, 2024)
The integration of Artificial Intelligence (AI) and Machine Learning (ML) into mental health care has gained significant attention in recent years, transforming how mental health disorders are diagnosed, treated, and managed. This research paper examines the multifaceted roles of AI and ML in enhancing mental health care, including their applications in early diagnosis, personalized treatment plans, and patient monitoring. The paper further explores ethical considerations, challenges, and future directions for AI and ML in mental health, emphasizing the need for collaboration between technology developers and mental health professionals. The findings indicate that AI and ML can significantly improve mental health outcomes, increase accessibility to care, and optimize resource allocation in mental health services.